Effects of Narrow-Windrow Burning on Weed Dynamics in Soybean in Louisiana - Patterson, Katie M.; Schwartz-Lazaro, Lauren M.; LaBiche, Gabrielle; Stephenson, Daniel O. (Frontiers in Agronomy, 2021)
The soil seedbank allows for long-term persistence of weed species in agricultural fields. Some weed species can persist in the soil seedbank for extended periods. Restricting inputs into the weed seedbank has a large impact on future population density and influences management practices of these weeds in soybean production systems. Harvest weed seed control (HWSC) tactics incorporate mechanical and cultural management strategies to target weed seeds present at harvest. A 3-year trial was initiated to determine if continual use of the HWSC method, narrow windrow burning, selects for earlier seed set and shattering in Louisiana soybean. No shifts in weed populations or shattering time were observed. However, there was a significant reduction in weed density and the weed seed present in the soil seedbank when HWSC and robust herbicide programs were used in combination. Therefore, utilizing multiple effective weed management strategies is imperative in reducing the soil seedbank.